MODERN METHODS, TOOLS AND MEANS OF MAKING ACCESSIBILITY OF ADDITIONAL EDUCATION OF CHILDREN OF VARIOUS CATEGORIES (FOR HEADS OF EDUCATIONAL ORGANIZATIONS) - A. Babich; R. Ter-Grigoryantz; G. Kotova (Вестник Северо-Кавказского федерального университета)
The article presents the results of a study of data of the system of additional education of children, and also outlines modern methods and tools to ensure its accessibility for children of all categories. The analysis and assessment of current indicators made it possible to identify new trends in the development of the system and anticipate the possible risks and consequences of the upcoming transformations. The study presents a methodology for increasing the accessibility of additional education for the leaders of educational organizations, implemented through specialized methods and tools. The author's position on the most effective use of accessibility tools for continuing education programs is presented through a network interaction model.